Pemahaman Perpajakan Bagi Pelaku Usaha Kecil - Nisrina, Ulfah Laila (Fakultas Ekonomi dan Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2025)
This study aims to explore the understanding of taxation among small business owners and how such understanding influences their tax compliance behavior. The research employs a qualitative descriptive approach, with data collected through in-depth interviews and direct observations involving small business actors who are actively engaged in business activities. The findings reveal that most small business owners possess a basic understanding of taxation, particularly regarding tax obligations and reporting procedures. However, their understanding remains limited and is often constrained by a lack of access to clear information, limited tax literacy, and the perception that tax regulations are complex. The study also finds that experience, social environment, and government outreach play important roles in shaping tax understanding among small business actors. Overall, the study highlights that improving tax education and providing continuous assistance are essential to enhancing tax awareness and voluntary compliance among small businesses.